The role of Equotherapy as auxiliar treatment tool in physical and psychiatric disorders: a narrative review (Research, Society and Development, 2023)
Equotherapy, also known as Hippotherapy (HPT), is a modality of therapy that uses horses as the main tool. Equotherapy provides several earnings to patients with cerebral palsy and autism spectrum disorder, such as increasing postural tonus and intellectual capability. However, the results achieved can be reproduced in patients with several physical and psychiatric disorders.  The purpose of this article is to review studies with reference to the practice of equine therapy by patients with different physical and psychiatric disorders and to verify the applicability of this therapy in the treatment of these conditions, as well as their main results. Pubmed and Embase databases were searched for articles on Hippotherapy since 2011, with 27 articles (including 19 systematic reviews) included. Their content includes cerebral palsy, autism spectrum disorder, down´s syndrome, mental and rheumatological disorders, and presents HPT as a promising tool in complementary therapy for these conditions. There are some HPT effects already known, such as improvements in emotional control, posture, and balance, besides self-esteem and quality of life improvements, effects of the feeling of empowerment and all the combined results.